65‐5: Improved Brightness and Efficiency of Green Quantum‐Rod‐Based Light‐Emitting Diodes. Issue 1 (28th June 2021) - Mallem, Kumar; Prodanov, Maksym F.; Chen, Dezhang; Marus, Mikita; Vashchenko,; Halpert, Jonathan E.; Srivastava, Abhishek K.
Abstract : Semiconductor colloidal quantum rods (QRs) are evolving as potential candidates for future lighting and display applications due to numerous advantages. QRs offer various aids over quantum dots (QDs) in terms of polarized emission, large global Stokes shift, and double the outcoupling efficiency. In this paper, we synthesized CdSe/CdS/ZnS (core/shell/shell) green QRs with an emission wavelength at 520 nm and employed them in QR based light‐emitting diodes (QRLEDs). The QRLED device performance was further optimized by inserting a thin poly (methyl methacrylate) (PMMA) layer in‐between emissive layer and electron transport layer (ETL) (ZnO NP). The PMMA layer is acting as a barrier between the emissive layers to the ETL interface, and thus limit the excess electron injection into the QRs and helps to maintain the balanced charge injection. The fabricated green QRLEDs exhibit excellent optoelectronic performance, such as high brightness of 11890 cd/m2 and an impressive peak external quantum efficiency (EQE) of 5.6 %. Through further tuning the device with a PMMA, we elevated the peak‐EQE up to 6.8%. To the best of our knowledge, these are the best‐reported numbers for the QR based green light‐emitting diodes.